2015
DOI: 10.5400/jts.2014.v19i2.67-73
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Height Waterlogging on Soil Physical Properties of Potential and Actual Acid Sulphate Soils

Abstract: Water management is main factor that determines the successful of rice cultivation in acid sulphate soil. Soil waterlogging determines the direction and rate of chemical, geochemical and biological reaction in the soil, indirectly these reactions may influence to the changes of soil psycal properties during soil waterlogging process. The experiment was aimed to study the changes of two type of acid sulphate soils physical properties during rice straw decomposition processes.  The  research  was  conducted  in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The porosity of a soil is inversely related to the soil bulk density, Li and Shao (2006) stated that soil bulk density was negatively correlated with total porosity, similar correlation of total soil porosity and bulk density have been showed by Fahmi et al (2014). The soil porosity is intimately related to soil permeability, increasing pore within soil particle increases soil permeability (Fahmi et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The porosity of a soil is inversely related to the soil bulk density, Li and Shao (2006) stated that soil bulk density was negatively correlated with total porosity, similar correlation of total soil porosity and bulk density have been showed by Fahmi et al (2014). The soil porosity is intimately related to soil permeability, increasing pore within soil particle increases soil permeability (Fahmi et al, 2014).…”
Section: Resultsmentioning
confidence: 80%
“…The changes in the soil's structure can be considered a diagnostic feature of the locally waterlogged chernozems (Tishchenko et al, 2013), but Fahmi et al (2014), showed that the soil waterlogging decreased aggregate stability, soil particle density and bulk density, but in not long waterlogging period, when studied the influence of height waterlogging on soil physical properties of potential and actual acid sulphate soils.…”
Section: Resultsmentioning
confidence: 99%
“…This process would produce high soil acidity and increase the solubility of iron and aluminum content, which may be harmful to cropsreported by Koesrini et al (2014) that applying lime with 2.0 Mg ha -1 is still required for increasing pH in the soil. Added by Fahmi et al (2014), the lime application was efficient in combination with good land preparation through intensive soil leaching and intermittent waterlogging. It was also reported by Ar-Riza et al (2015) that the main problem is challenging to get fresh water for the leaching and flushing process.…”
Section: Computer Simulation Of Drainmod In Estimating Soil Water Tablementioning
confidence: 99%
“…One relatively less productive area is Sugihan Kanan, with a rice production level of fewer than 3 Mg.ha -1 , and most of its agricultural land had one planting index (Imanudin et al 2016). The soil is classified as acid sulfate soil, with high acidity and Alumunium content (Fahmi et al 2014). Aluminum toxicity has produced an alteration of biochemical and physiological reactions of plants and then to their crop productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation